2012
DOI: 10.1183/09031936.00204311
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of deep inspiration-induced bronchoprotection: evidence from a mouse model

Abstract: In healthy individuals, deep inspirations (DIs) taken prior to a bronchial challenge reduce the bronchoconstrictor response, which is termed ''bronchoprotection''. The mechanism(s) of DI-induced bronchoprotection is unclear.The forced oscillation technique was used to assess the effect of prior DI on subsequent bronchoconstriction to methacholine (MCh) in BALB/c mice. We assessed likely mechanisms for the bronchoprotective effects of DI including reduced airway narrowing (from changes in airway resistance) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…The present lack of evidence for a dominant effect of ASM length adaption in situ is consistent with the failure of simulated DI to induce bronchoprotection in airway segments. The implication of these observations is that bronchoprotective effects of DI in vivo may instead arise from one or more mechanisms other than length adaptation, notably enhanced bronchodilatory effects to DI when bronchoconstriction is assessed by forced expiratory volume in 1 s (FEV 1 ), prevention of airway closure, or both (9,60). With respect to the bronchodilatory effects elicited by DI in airway segments (36,58), our present findings favor mechanisms other than length adaptation, such as crossbridge perturbation (16,17).…”
Section: Implications For Bronchoprotective and Bronchodilatory Effecmentioning
confidence: 52%
“…The present lack of evidence for a dominant effect of ASM length adaption in situ is consistent with the failure of simulated DI to induce bronchoprotection in airway segments. The implication of these observations is that bronchoprotective effects of DI in vivo may instead arise from one or more mechanisms other than length adaptation, notably enhanced bronchodilatory effects to DI when bronchoconstriction is assessed by forced expiratory volume in 1 s (FEV 1 ), prevention of airway closure, or both (9,60). With respect to the bronchodilatory effects elicited by DI in airway segments (36,58), our present findings favor mechanisms other than length adaptation, such as crossbridge perturbation (16,17).…”
Section: Implications For Bronchoprotective and Bronchodilatory Effecmentioning
confidence: 52%
“…One interpretation of this discrepancy is that prior DI may not alter the initial airway narrowing produced by a constrictor but instead make the ASM more responsive to subsequent strain during the DI required to perform an FEV 1 maneuver. This potential mechanism is supported by a recent study of the effect of DI in mice [83]. …”
Section: Airway Smooth Muscle Adaptabilitymentioning
confidence: 53%
“…In this line, Thammanomai et al ( 2008 ) showed that, in injured mice, variable ventilation, but not conventional ventilation with periods of large breaths, resulted in less lung inflammation. In emphysema, a substantial degree of small airway narrowing can be present (McDonough et al, 2011 ), but deep inspirations, which are present sporadically during VV, have been shown to revert this (Wong et al, 2012 ). In addition, the fact that VV applies subphysiological V T values may have helped limit hyperinflation during mechanical ventilation and promote emptying of lung regions with lower time constants.…”
Section: Discussionmentioning
confidence: 99%